Phytoplankton structure in two contrasting cascade reservoirs (Paranapanema River, Southeast Brazil) - Perbiche-Neves, Gilmar [UNESP]; Romero Ferreira, Rosa Antonia [UNESP]; Nogueira, Marcos Gomes [UNESP] (Versita, 2011)
A series of eleven reservoirs was constructed in the Paranapanema River, southeast Brazil, for hydropower production. The phytoplankton structure and its relations with the environmental variables were studied in two of these reservoirs: a large upstream located storage system (high water retention time) and a small run-of-river system (short water retention time). The samples were collected quarterly for two consecutive years, at four sampling stations in each reservoir. Higher phytoplankton richness was observed in the semi-lotic compartments. Higher values of diversities were observed in the upper region of the run-of-river reservoir, under the influence of the larger storage reservoir discharges, and lower values were observed in deeper layers of this same reservoir. The pronounced variation on seasonal rain precipitation and operational water releases, retention time and quota had major influence in the phytoplankton assemblages. The influence of other environmental variables was also indicated by a canonical correlation analysis. Chlamydophyceae, Dinophyceae, Zygnemaphyceae, Chrysophyceae, Chlorophyceae, Bacillariophyceae and Cyanobacteria were positively correlated with higher transparency and depth; Euglenophyceae with temperature and Cryptophyceae with total phosphorus, dissolved oxygen, conductivity, turbidity, total nitrogen and total suspended solids. The influence of the storage reservoir on the phytoplankton of the downstream run-of-river reservoir was more evident in the dry period. During the rainy period the lateral tributaries effects seems to have a higher influence, especially on the smaller studied reservoir.
Keywords: phytoplankton; run-of-river reservoir; spatial variation; storage reservoir; temporal variation